Anti-Inflammatory Potential of n-3 Polyunsaturated Fatty Acids Enriched Hen Eggs Consumption in Improving Microvascular Endothelial Function of Healthy Individuals—Clinical Trial - Stupin, Ana (Int J Mol Sci, 2020)
The effects of consumption of n-3 polyunsaturated fatty acids (n-3 PUFAs) enriched hen eggs on endothelium-dependent and endothelium-independent vasodilation in microcirculation, and on endothelial activation and inflammation were determined in young healthy individuals. Control group (N = 21) ate three regular hen eggs/daily (249 mg n-3 PUFAs/day), and n-3 PUFAs group (N = 19) ate three n-3 PUFAs enriched hen eggs/daily (1053 g n-3 PUFAs/day) for 3 weeks. Skin microvascular blood flow in response to iontophoresis of acetylcholine (AChID; endothelium-dependent) and sodium nitroprusside (SNPID; endothelium-independent) was assessed by laser Doppler flowmetry. Blood pressure (BP), body composition, body fluid status, serum lipid and free fatty acids profile, and inflammatory and endothelial activation markers were measured before and after respective dietary protocol. Results: Serum n-3 PUFAs concentration significantly increased, AChID significantly improved, and SNPID remained unchanged in n-3 PUFAs group, while none was changed in Control group. Interferon-γ (pro-inflammatory) significantly decreased and interleukin-10 (anti-inflammatory) significantly increased in n-3 PUFAs. BP, fat free mass, and total body water significantly decreased, while fat mass, interleukin-17A (pro-inflammatory), interleukin-10 and vascular endothelial growth factor A significantly increased in the Control group. Other measured parameters remained unchanged in both groups. Favorable anti-inflammatory properties of n-3 PUFAs consumption potentially contribute to the improvement of microvascular endothelium-dependent vasodilation in healthy individuals.